Demographic and onco-epidemiological situation in radioactive contaminated territory of Zhytomyr Oblast - L. O. Herasymchuk; G. M. Martenyuk; R. A. Valerko; M. M. Kravchuk (Regulatory Mechanisms in Biosystems, 2019)
We performed an assessment of demographic parameters of occurrence of malignant tumours and mortality of the population which lives in the radioactive contaminated territory of Zhytomyr Oblast (Yemilchynskyi, Luhynskyi, Narodytskyi, Korostenskyi, Olevskyi, and Ovrutskyi districts) over a 32-year period (1985–2017). The source material for the study of the demographic situation and malignant tumours in the population of the radioactive contaminated administrative districts of Zhytomyr Oblast during 1985–2017 was the statistical data of the Management of Healthcare of Zhytomyr Oblast State Administration, Central Department of Statistics in Zhytomyr Oblasts, reports on occurrences of malignant tumours of the state institution Center of Medical Statistics of the Ministry of Healthcare of Ukraine, data of the Radiological Control Service in Zhytomyr Oblast. It was determined that over 1985–2017 in the radioactive contaminated territory of Zhytomyr Oblast, a natural decline of population was observed, maximum values of which occurred in 2005 (except Narodnytsky district – 2000). The highest levels of occurrence of tumours and mortality caused by them among the adult population were observed 14 years after the Chornobyl nuclear power plant disaster. The peak of the occurrence of malignant tumours among children in the radioactive contaminated territory of Zhytomyr Oblast was observed 9 years after the explosion. A relationship was determined between doses of irradiation of the population and the risk of occurrence of malignant tumours in the radioactive contaminated regions of Zhytomyr Oblast. Taking into account that the method of calculation of passport dose (average annual effective dose of irradiation) was developed 23 years ago, nowadays it can lead to errors. This is related to change in amounts of consumption of different products by the population, which needs to be considered when determining radiological risks. The obtained data indicate that analysis of demographic and onco-epidemiological consequences of the Chornobyl catastrophe remains a relevant issue nowadays and will remain so in the near future.